Modified dot-blot hybridization technique for filamentous fungi. - C. R. McClung; J. C. Dunlap (Fungal Genetics Reports, 1988)
Colony hybridization (Grunstein & Hogness, 1975 Proc. Nat. Acad. Sci. USA 72:3961-3965) A allows the rapid screening of multiple strains for the presence or absence of particular DNA sequences.